2021
DOI: 10.15655/mw/2021/v12i3/165405
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Social Media Influencer Marketing On Youth Purchase Intentions in UAE

Abstract: The study analyses how youth perceive social media Influencers and whether they affect their purchasing intentions and buying decisions. It also measure s influencers' attractiveness, expertise, and trustworthiness while communicating with consumers. In addition, the study explores the types of digital interaction with influencers, measures the impact of their online marketing activities on purchasing intentions, and finds differences between youth demographic segments. A total of 350 youth participants in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 31 publications
(35 reference statements)
1
11
0
1
Order By: Relevance
“…Recently, the studies concerning social network usage also executed and found the Theory of Reasoned Action as describing primary yet fundamental factors determining adoption, particularly a certain technology adoption process. Similarly, adopting social networks by the Public Relations practitioners indicated a similar phenomenon in this study, where cognitive beliefs are attributed to behavioral adoption leading to expectations fulfillment (Radwan et al, 2021). In this regard, these findings also showed potential consistency with the existing literature, providing an overview of the relevance of the Theory of Reasoned Action with adopting the social network.…”
Section: Discussion On Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…Recently, the studies concerning social network usage also executed and found the Theory of Reasoned Action as describing primary yet fundamental factors determining adoption, particularly a certain technology adoption process. Similarly, adopting social networks by the Public Relations practitioners indicated a similar phenomenon in this study, where cognitive beliefs are attributed to behavioral adoption leading to expectations fulfillment (Radwan et al, 2021). In this regard, these findings also showed potential consistency with the existing literature, providing an overview of the relevance of the Theory of Reasoned Action with adopting the social network.…”
Section: Discussion On Resultssupporting
confidence: 84%
“…Especially, building the relevant assumption on the Theory of Reasoned Action, it is shown that cognitive Attitude works as a primary determinant of the adoption process that determines the adoption and usage purposes. Existing research on the Theory of Reasoned Action indicates individuals hold cognitive beliefs that assume the goals are fulfilled according to their expectations and demands (Radwan et al, 2021).…”
Section: Discussion On Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Youths' intention to engage in internet trade might be influenced by second-hand information from social influence and other influential people. Past researchers have found a positive correlation between how social influence and influencers can positively influence the youth's intention (Radwan et al, 2021;Telzer et al, 2018).…”
Section: Findings and Discussionmentioning
confidence: 97%
“…Lebih lanjut menurut penelitian Afandi, et al (2021) ia mengemukakan bahwa influencer berpengaruh terhadap keputusan pembelian pada generasi Z. studi ini telah menunjukkan bahwa keputusan pembelian yang dilakukan generasi Z dipengaruhi oleh faktor influencer khususnya dalam indikator penampilan dan pengalaman seorang influencer. Didukung penelitian oleh Radwan, et al (2021) serta penelitian oleh Zak dan Hasprova (2020) yang menyatakan bahwa influencer memiliki dampak pada keputusan pembelian.…”
Section: Pendahuluanunclassified